On lacunary statistical convergence of order ? - Şengül, Hacer; Et, Mikail (My University, 2014)
In this article, we introduce the concept of lacunary statistical convergence of order ? of real number sequences and give some inclusion relations between the sets of lacunary statistical convergence of order ? and strong N??(p)-summability. Furthermore, some relations between the spaces N?? S?? are examined. © 2014 Wuhan Institute of Physics and Mathematics.
Keywords: Cesàro summability; Lacunary sequence; Statistical convergence